Diphenyleneiodonium inhibits NF-kappaB activation and iNOS expression induced by IL-1beta: involvement of reactive oxygen species - Mendes, A. Ferreira (2001)
AIMS: In this work, we studied the mechanisms by which diphenyleneiodonium chloride (DPI) inhibits nitric oxide (NO) synthesis induced by the proinflammatory cytokine interleukin-1beta (IL-1) in bovine articular chondrocytes. To achieve this, we evaluated the ability of DPI to inhibit the expression and activity of the inducible isoform of the NO synthase (iNOS) induced by IL-1. We also studied the ability of DPI to prevent IL-1-induced NF-kappaB activation and reactive oxygen species (ROS) production. RESULTS: Northern and Western blot analysis, respectively, showed that DPI dose-dependently inhibited IL-1-induced iNOS mRNA and protein synthesis in primary cultures of bovine articular chondrocytes. DPI effectively inhibited NO production (IC50=0.03+/-0.004 microM), as evaluated by the method of Griess. Nuclear factor-kappa B (NF-kappaB) activation, as evaluated by electrophoretic mobility shift assay, was inhibited by DPI (1-10 microM) in a dose-dependent manner. IL-1-induced ROS production, as evaluated by measurement of dichlorofluorescein fluorescence, was inhibited by DPI at concentrations that also prevented NF-kappaB activation and iNOS expression. CONCLUSIONS: DPI inhibits IL-1-induced NO production in chondrocytes by two distinct mechanisms: (i) by inhibiting NOS activity, and (ii) by preventing iNOS expression through the blockade of NF-kappaB activation. These results also support the involvement of reactive oxygen species in IL-1-induced NF-kappaB activation and expression of NF-kappaB-dependent genes, such as iNOS